Silencing the Subaltern: Representation of Women in Chinua Achebe’s Things Fall Apart - Baral, Rohit Prasad (The Outlook: Journal of English Studies, 2026)
This paper studies the roles of women characters in Chinua Achebe’s Things Fall Apart to explore the position and challenges of women in Nigerian society. Through an analysis of female characters, the study reveals how women are marginalized and denied the freedom to express themselves. When Ekwefi, the wife of Okonkwo, disagrees with the decision to slaughter only one goat instead of two for a feast, her opinion is harshly dismissed, and she is forcefully silenced by her husband. To analyse such problems of women, the paper draws on Gayatri Chakravorty Spivak’s concept of the subaltern, particularly her question, “Can the Subaltern Speak?” It also employs Simon de Beauvoir’s concept of women as “the Other” to strengthen the research argument. The paper argues that women in Nigerian culture are subjected to severe patriarchal suppression. Whenever they attempt to voice their opinions, they are frequently ignored, ridiculed, or silenced by men. In addition to patriarchal domination, economic deprivation further restricts their ability to speak and assert themselves. As a result, they remain unable to cross the rigid boundaries imposed by masculinity. The paper concludes that the women characters in the novel are oppressed through practices of silencing, ignoring, ridiculing, and commodifying. Since the novel reflects the realities of Nigerian society, this condition represents a subaltern state in which women are denied agency and voice. The study suggests that women can achieve empowerment only by resisting such oppression and speaking for themselves.